2003
DOI: 10.1017/s1355617703970056
|View full text |Cite
|
Sign up to set email alerts
|

Learning in children and sleep disordered breathing: Findings of the Tucson Children's Assessment of Sleep Apnea (TuCASA) Prospective Cohort Study

Abstract: We examined the relationship between nocturnal respiratory disturbance and learning and compared learning in children with and without nocturnal respiratory disturbance. Subjects were 149 participants in a prospective cohort study examining sleep in children ages 6-12: The Tucson Children's Assessment of Sleep Apnea study (TuCASA). Sleep was assessed via home polysomnography. Intelligence, learning and memory, and academic achievement were assessed. Parents rated attention. Group comparisons were used to test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
3

Year Published

2005
2005
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(123 citation statements)
references
References 27 publications
5
111
1
3
Order By: Relevance
“…In the present study, the AHI was adopted for the diagnosis and classification of OSAS for the following reasons: first, because it is relatively uncommon to observe complete obstruction of the upper airways in children; second, because in a study involving OSAS children (diagnosed on the basis of the AHI), the authors reported that the children in which hypopnea was not accompanied by desaturation events had low cognitive scores (6) ; third, because in this same study, the children in which hypopnea was accompanied by desaturation events presented arterial hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the AHI was adopted for the diagnosis and classification of OSAS for the following reasons: first, because it is relatively uncommon to observe complete obstruction of the upper airways in children; second, because in a study involving OSAS children (diagnosed on the basis of the AHI), the authors reported that the children in which hypopnea was not accompanied by desaturation events had low cognitive scores (6) ; third, because in this same study, the children in which hypopnea was accompanied by desaturation events presented arterial hypertension.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the mean IQ in the OSAS population was significantly above the standard mean. Some [32][33][34] but not all studies showed a correlation between the severity of obstructive apnea as measured on PSG and increasing neuropsychological morbidity. There are several reasons why correlations were not found for all studies.…”
Section: Cognitive Deficitsmentioning
confidence: 98%
“…[32][33][34]39 Cognitive deficits associated with pediatric SDB include general intelligence level as well as processes measured by using IQ subtests (Table 8). Specific functions objectively measured by using neuropsychological assessments and included in the research studies include:…”
Section: Cognitive Deficitsmentioning
confidence: 99%
“…Sleep fragmentation and sleep-disordered breathing may adversely impact on a child's cognitive performance, learning and memory, and academic learning [10]. As a result these children may also experience excessive daytime sleepiness and/or hyperactivity [29].…”
Section: Leisure Participation 14mentioning
confidence: 99%